The relationship between personality types and learning styles among the technical and vocational (TVE) students in University Technology Malaysia - 565319 Widad Othman; Rio Sumarni Shariffuddin; Lee, Ming Foong; International Literacy Conference (3rd : 2003 : Pulau Pinang) (Skudai : Universiti Teknologi Malaysia, 2003)
44